Caderno ateliê : reflexões sobre metodologias operativas no estúdio de pintura - Lampert, Jociele (2018)
Understanding space and time of the painting studio as a teaching and learning laboratory in the Visual Arts has been the goal of our practices as teachers in the face of research. First of all, it is to map operational methodologies of those who teach and learn painting, the painting studio being an experimental laboratory, where art as experience is the core of the reflection on the pictorial process. This subject pervades the construction of the image and the production of visual thought, as well as of the methodological ways of teaching painting, entering the creative process beyond a mere technical lesson. It is a question of reflecting on the context of contemporary education, presupposing the transit or interlocution between painting and Art Education, or about the formation of the teacher and the artist. These practices, or the quest for the understanding of Art as experience, derive from our studies in John Dewey, as well as from the challenges encountered where we stand: in university education